METABOLISME PREBIOTIK OLEH KANDIDAT PROBIOTIK ISOLAT ASI SEBAGAI DASAR PENGEMBANGAN PRODUK SINBIOTIK [Prebiotics Metabolism by Probiotics Candidates Isolated from Breast Milk as a Basis for Development of Sinbiotics Product] - Lilis Nuraida; Nur Rita Mardiana; Didah Nur Faridah; Hana . (Jurnal Teknologi dan Industri Pangan, 2011)
Five Lactobacillus strains and two Pediococcus strains isolated from breast milk were evaluated for their ability to metabolite oligosaccharide known as prebiotics, i. e. inulin, FOS, GOS, FOS:GOS (1:9), and inulin:GOS (1:9). The result shows that all Lactobacillus and Pediococcus strains were able to grow in medium with prebiotics as carbon sources. The best growth was observed when GOS or FOS were used as carbon source, while inulin was the worst. The best growth in all oligosaccharides was observed in Lactobacillus R23H, followed by L. rhamnosus B16, L. rhamnosus R23, and L. rhamnosus R14. Further study on R23H (heterofermenter) and R23 (homofermenter) shows that there was no difference in metabolizing oligosaccharides between heterofermenter and homofermenter. GOS was the best prebiotic used by the both lactic acid bacteria as shown by rapid decrease of total sugar. The reducing sugar in medium containing GOS was higher than other oligosaccharides. The decrease of total sugar in medium containing inulin was the slowest, indicating that inulin was the most difficult prebiotic to be metabolized by the lactic acid bacteria. When inulin mixed with GOS in the ratio 1:9, the rate of decreasing of total sugar in the medium was similar to the medium with GOS as single carbon source, however it cannot be distinguished if the role of inulin took place after GOS disappeared. The rate of sugar metabolism was in accordance with the growth of lactic acid bacteria isolates in medium containing prebiotics. L. rhamnosus R23 was used in sinbiotic fermented milk product combine with FOS, inulin, and inulin:GOS (1:9). After fermentation, remaining sugar in skim milk with additional prebiotics was higher than skim milk without additional prebiotics. Remaining sugar on fermented milk product includes the amount of prebiotic that will be used as carbon source in colon. Combination of potential probiotic L. rhamnosus R23 and mixture of inulin:GOS (1:9) could be used to make sinbiotic fermented milk product.